RISK FACTOR ASSESSMENT OF NON-COMMUNICABLE DISEASES USING COMMUNITY BASED ASSESSMENT CHECKLIST AMONG KASHMIRI ADULT POPULATION - Nabi, Sahila; Nisar, Iqra; QAZI, TANZEELA BASHIR; SALIM KHAN, MUHAMMAD (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The Objective of the study was to assess the risk factors of non-communicable diseases (NCDs) using community based assessment checklist (CBAC) form among Kashmiri adults. Methods: This was a community based cross sectional study conducted in the field practice area of department of community medicine, Government medical college Srinagar over a period of 3 months. Results: Among the total of 601, 212 (34.7%) were found to have high risk and 398 (65.2%) were found to have low risk. Majority (38.6%) of the high-risk patients were in the age group of 41–50 years. Age, gender and educational level was significantly associated with high-risk participants with a p<0.001. Tobacco consumption, physical inactivity and presence of NCD were significantly higher among high-risk participants. Conclusion: 34.7% of the study participants were found to have high risk on CBAC assessment. CBAC is a very simple tool that can be used to screen the risk of NCDs in communities by ASHA workers.